Building area studies collections - Hazen, Dan C.; Spohrer, James H. (Beiträge zum Buch- und Bibliothekswesen, 2007)
These essays by noted Area Studies specialists at a number of US research libraries serve as a practical and theoretical guide to university and college administrators, library directors and heads of collection development, as well as selection practitioners who work to create foreign-language collections for research libraries. The volume constitutes a general introduction for new practitioners and even the most experienced Area Studies librarians will find useful practical advice for reviewing and refining their existing collecting practices. Coverage includes East Asia, Latin America, Southeast Asia, Africa, South Asia and the Romance language areas of Europe, as well as the German/Nordic/Netherlandic countries. Each essay presents the Area Studies topic in question from an historical perspective and provides background on its present status and anticipated future development. Special emphasis is placed on the techniques of both print and digital collecting and on the assessment methods by which collection strengths and future needs are determined. Guidelines for expenditures for both collections and collateral activities such as providing access and preservation are provided, and contributors also supply extensive documentation for the burgeoning array of online digital resources which have emerged in the past decade. The volume editors, Dan C. Hazen (Harvard) and James H. Spohrer (University of California, Berkeley), also provide a general introduction to the topic and a detailed summary of current cooperative activities in Area Studies collecting.